An Oxidant- and Catalyst-Free Synthesis of Dibenzo[a,c]carbazoles via UV Light Irradiation of 2,3-Diphenyl-1H-indoles - Kang, Yang; Hou, Rong; Min, Xiaoyan; Wang, Tao; Liang, Yong; Zhang, Zunting (Synthesis, 2021)
An efficient methodology for the synthesis of dibenzo[a,c]carbazoles via annulation of 2,3-diphenyl-1H-indoles in EtOH under UV light irradiation (λ = 365 nm) along with hydrogen evolution is described. This method exhibits the advantages of mild reaction conditions, no requirement of any oxidants and catalysts, and release of hydrogen as the only byproduct. Notably, the mechanism investigation confirms that the trans-4b,8a-dihydro-9H-dibenzo[a,c]carbazole intermediate could convert into cis-4b,8a-dihydro-9H-dibenzo[a,c]carbazole, which relies on the nitrogen atom of the indole ring. This is followed by intramolecular dehydrogenation which yields the dibenzo[a,c]carbazoles.
Keywords: photocyclization; 2,3-diphenyl-1H-indoles; hydrogen evolution; [1,5]-H shift; dibenzo[a,c]carbazoles